Natural Occurrence of Escherichia coli-Infecting Bacteriophages in Clinical Samples - Pacífico, Cátia; Hilbert, Miriam; Sofka, Dmitrij; Dinhopl, Nora; Pap, Ildiko-Julia; Aspöck, Christoph; Carriço, João André; Hilbert, Friederike (Frontiers in Microbiology, 2019)
The interaction between bacteriophages, bacteria and the human host as a tripartite system has recently captured attention. The taxonomic diversity of bacteriophages, as a natural parasite of bacteria, still remains obscure in human body biomes, representing a so-called “viral dark matter”. Here, we isolated and characterized coliphages from blood, urine and tracheal aspirates samples collected at a tertiary care hospital in Austria. Phages were more often isolated from blood, followed by urine and tracheal aspirates. Phylogenetic analysis and genome comparisons allowed the identification of phages belonging to the Tunavirinae subfamily, and to the Peduovirus and Tequintavirus genera. Tunavirinae phages cluster together and are found in samples from 14 patients, suggesting their prevalence across a variety of human samples. When compared with other phage genomes, the highest similarity level was at 87.69% average nucleotide identity (ANI), which suggests that these are in fact a newly isolated phage species. Tequintavirus phages share a 95.90% with phage 3_29, challenging the ANI threshold currently accepted to differentiate phage species. The isolated phages appear to be virulent, with the exception of the Peduovirus members, which are integrative and seem to reside as prophages in bacterial genomes.